Mental Health Professionals’ Stigmas towards People with Mental Health Issues in Saudi Arabia - Alyousef, Ph.D., Seham Mansour (International Journal of Innovative Research in Medical Science, 2017)
Most of the people with mental issues suffer not only from the specific symptoms of their condition but also by the way in which they are perceived in the world. The purpose of this study is to develop a thorough understanding of the prejudices and stereotypes held by mental health professionals about patients receiving mental health care. A qualitative approach was applied in Psychiatric and mental health department at University Hospital, in Riyadh. Data was collected from a focus group comprised of ten health care professionals, working in different mental health professions. Data was analyzed using Nvivi.10 thematic content analysis. Participants completed a demographic data sheet. Content analysis identified major themes. The focus group was asked to provide concrete examples of stigma towards people with mental health issues and to consider how the prejudices arise in mental health care professionals. Results reveal five factors that foster stigmas: Negative feelings; attitude, diagnosis; relationships; and stigma experiences within marital relationships. This research explores the stigmas among mental health professionals of people with mental health problems concerning providing mental health services in Saudi Arabia. Much work still needs to be done to understand the breadth and scope of professional prejudice, discrimination and stigma against people with mental health problems thoroughly.